The Effectiveness of KAPRA Learning Model on Buffer Solution to improve Students' Critical Thinking Skills - Maria Erna; Lenny Anwar; Durriah Durriah (Jurnal Tadris Kimiya, 2021)
This study analyzes the effectiveness of the KAPRA learning model (associate, experience, think, negotiate, and apply) students' critical thinking skills on buffer solutions. The subjects of this research are students of class XI MIPA 3 as the experimental and class XI MIPA 4 as the control class at SMAN 10 Pekanbaru. The method uses experimental research with a randomized control group pretest-posttest research design. The data obtained were analyzed using normality test, homogeneity test, hypothesis testing and N-Gain test. The results showed that the KAPRA learning model effectively increased students' critical thinking skills. Based on the hypothesis test, tcount > ttable (5.89 > 1.66) with the N-Gain value in the moderate category of 0.52.